[Cows in field] (1913)
View from the cow fields on the east side of campus, looking west. The Weeks Administration Building can be seen in the distance with the other original campus buildings. Taken at approximately the same time as this panorama: https://digital.lib.calpoly.edu/rekl-11397, possibly photographed by Frank Aston.